A courtship to fool Manhattan - Robinson, Lauri (Harlequin, 2024)
A pretend courtship... To prevent a marriage! At his sister's society wedding, Lincoln Dryer finds himself paired up with heiress Victoria Biggs. Tired of being matchmade, Lincoln is surprised to learn Victoria feels the same. So they agree to pretend to be a couple! Though he enjoys Victoria's refreshing company, Lincoln's seen the heartache love can cause... Yet while their charade fools Manhattan, how long can Lincoln fool himself into believing he can let Victoria go when the wedding party's over?